A measure of functioning in adults With ADHD: Psychometric properties of the general life functioning scale‐parent version. Issue 12 (3rd December 2021) - Zhao, Xin; Kennedy, Traci M.; Hayes, Timothy; Gnagy, Elizabeth M.; Pelham, William E.; Molina, Brooke S. G.
Abstract: Objective: The General Life Functioning Scale (GLF) was developed to provide a complementary alternative to existing measures of impairment. We examined the psychometric properties of the GLF‐Parent version (GLF‐P), given the known value of informant ratings. Methods: The GLF‐P was administered to parents of adults with attention‐deficit/hyperactivity disorder (ADHD) diagnosed in childhood and a nonADHD comparison group in the Pittsburgh ADHD Longitudinal Study. GLF‐P ratings described 334 participants (ADHD = 186; comparison = 148) rated at age 25 ( M age  = 24.80 years, SD age  = 0.46, range = 24–26) and 401 participants (ADHD = 237; comparison = 164) rated at age 30 ( M age  = 29.30, SD age  = 0.64, range = 28–33). Exploratory (EFA) and confirmatory (CFA) factor analyses were used. Results: EFAs suggested and CFAs confirmed a five‐factor solution. We found measurement invariance across diagnostic and age groups, satisfactory internal consistency, construct validity, and known‐group validity. Conclusion: Psychometric results suggest the GLF‐P as a helpful adjunctive measure of functioning. Further research is needed to determine the utility of the GLF across diverse settings.